REEVALUATING PREVIOUS CONCEPTS OF “THE NATION” - Izolda Takács (European Scientific Journal, ESJ, 2015)
In my hypothesis the concept of the nation is present, and it could be defined precisely in Széchenyi’s work. The aim of my paper is to prove, or to cast way this hypothesis. My statement will be supported by quotes from Széchenyi. In my opinion our image and concept of the Hungarian nation has been made up by nation concepts like these. They come to the forefront more and more. Namely, the analysis of the nation concept of the “greatest Hungarian” could make us more aware of the genealogy of our Hungarian national consciousness.